Experimental 1H and 13C Solid-State NMR Signal Assignment of Paramagnetic Copper (II) 2-Pyrazine-Carboxylate Complex using Density Functional Theory Calculations. Issue 1 (March 2021) - Patil, Bhargava Hanumanta; Peraje, Pampa; Naik, Dinesh; Rajaramakrishna, R; Dittmer, Jens; Kumara Swamy, Shashi Kumar
Abstract: We have acquired 1 H and 13 C solid-state NMR (ssNMR) spectra of the paramagnetic Cu(II)-2-pyrazine-carboxylate (Cu-Py) complex and assigned paramagnetic 1 H/ 13 C signals using density functional theory (DFT) calculations. The unpaired electron in Cu(II) ionexacerbates the 1 H and 13 C chemical shifts in the Cu-Py complex through hyperfine interactions, making the conventional NMR signal assignment non-feasible. Further, the nuclear fast relaxation in paramagnetic metal-organic system hampers application of routine ssNMR techniques for signal acquisition. In our work we have employed simple DEPTH experiment at 50 kHz magic angle spinning (MAS) for acquiring 1 H and 13 C 1D ssNMR spectra of the paramagnetic Cu(II)-2-pyrazine-carboxylate (Cu-Py) complex. The paramagnetic augmented (diamagnetic chemical shift + paramagnetic shift) 1D 1 H and 13 C ssNMR signals (shifts) from Cu-Py complex have major contribution from Fermi contact interaction due to proximity of the organic arm to Cu 2+ ion (Cu 2+ -C/H atoms 0-5 Å). The unpaired electron spin density distributed over the pyrazine-carboxylate organic arm is crucial in understanding Fermi contact shifts and hence accounts for 1 H and 13 C ssNMR signal assignment. The theoretical Fermi contact shifts together with diamagnetic shifts, calculated using density functional theory (DFT) at B3LYP level with basis sets viz. 6-311G, 6-311G+(D) and 6-311G++(D), were compared with the experimental shifts to facilitate the process of signal assignment. Vibrational analysis of Cu-Py complex was performed at B3LYP level of theory with various basis sets in comparison with experimental IR data. This further assisted in double validation of DFT optimized Cu-Py structure used here for extracting Fermi contact shifts. Furthermore molecular orbital analysis on the DFT optimized Cu-Py structure articulates the spin density distribution mechanism, thereby stipulating the location of the unpaired electron in the Cu(II) dx 2 -y 2 orbital in Paramagnetic Cu-Py complex.